DETERMINASI BRAND EQUITY DAN IMPULSE BUYING TERHADAP KEPUTUSAN PEMBELIAN PADA BISNIS DIGITAL E-COMMERCE - Wirawan, Soni; Syahputra, Hendra (Growth, 2024)
This study aims to identify the influence of brand equity and impulse buying on purchasing decisions in the context of e-commerce, and explore the synergistic use of these two factors to improve business performance. Focusing on Shopee application users in Bondowoso and Situbondo, totaling 22,550, this study adopted the proportional random sampling method and used the Slovin formula to determine a sample of 131 users. Path analysis was conducted using the IBM AMOS program after the data was tested for validity and reliability with SPSS. The results showed that brand equity has a positive and significant influence on purchasing decisions. Likewise, impulse buying shows a positive and significant influence on purchasing decisions. This study opens up opportunities to explore the impact of these two factors on different consumer segments, such as age and digital literacy levels. These findings are expected to provide practical insights for e-commerce business actors in designing attractive and sustainable marketing strategies, and emphasize the importance of building strong brand equity in facing increasingly tight e-commerce industry competition.